Features and Fillers Texas Journalists on Texas Folklore - Satterwhite, Carolyn Fiedler; Harris, Jim, 1942-; Project Muse. (University of North Texas Press, 1999)
Discusses El ojo, Rattlesnake roundups, and chicken-fried steak, and other important novelties of Texas.
Dedication / Paul Patterson -- Texas Journalists on Texas Folklore / Jim Harris -- A Legend Runs Through It / Bryan Woolley (The Dallas Morning News) -- The Weeping Woman / John O. West (The Fort Worth Star-Telegram) -- Bois d'Arc Recollections / Ernestine Linck, Charles Linck (The Commerce Journal) -- Prescriptions for Ailments Did Not Always Find a Cure and Dyin' Easy and Several Other Ways of Crossing Over and Departing This Life / Joyce Gibson Roach (The Fort Worth Star-Telegram) -- Musing on Distant, Faded Glories of the Days of Radio / Robert J. Duncan (The Fort Worth Star-Telegram) -- Unknowingly, Security Guard Takes on KKK / Robert J. Duncan (McKinney Courier Gazette) -- Four Musings on Bad Roosters / Henry Wolff, Jr. (The Victoria Advocate) -- The Ol' Red Rooster Learns a Hard Lesson / Lora B. Garrison (Uvalde Leader-News) -- Hallie Stillwell Will Live on in Memories / Kent Biffle (The Dallas Morning News) -- Ex-Sheriff's Tale Is One for History Books / Kent Biffle (The Dallas Morning News) -- Tales of a Rural School Teacher / Lou Rodenberger (The Fort Worth Star-Telegram) -- The New Year Hasn't Always Started January 1; Valentine's Day: How It All Began; and Columbus Day Roots Are in This Century / Archie McDonald (The Daily Sentinel) -- Texas' Oddest Animal / Jerry Turner (The Mexia Daily News) -- What Mrs. Rives Found in Gilmer / Sarah Greene (The Gilmer Mirror) -- He 'Woodn't' Trade Hobby for Anything / John Fooks (The Texarkana Gazette).
Includes index.
Description based on print version record.
Keywords: Social Sciences; Folklore; Anthropology; Folklore; American newspapers; Folklore -- Press coverage -- Texas; Folklore -- Texas; American newspapers -- Texas; Folklore -- Press coverage -- Texas; Folklore -- Texas; Texas; Texas -- Folklore and legends; Electronic books; Electronic books